Assessment of wheelchair driving performance in a virtual reality-based simulator. (July 2013) - Mahajan, Harshal P.; Dicianno, Brad E.; Cooper, Rory A.; Ding, Dan
Abstract : Objective: To develop a virtual reality (VR)-based simulator that can assist clinicians in performing standardized wheelchair driving assessments. Design: A completely within-subjects repeated measures design. Methods: Participants drove their wheelchairs along a virtual driving circuit modeled after the Power Mobility Road Test (PMRT) and in a hallway with decreasing width. The virtual simulator was displayed on computer screen and VR screens and participants interacted with it using a set of instrumented rollers and a wheelchair joystick. Driving performances of participants were estimated and compared using quantitative metrics from the simulator. Qualitative ratings from two experienced clinicians were used to estimate intra- and inter-rater reliability. Results: Ten regular wheelchair users (seven men, three women; mean age ± SD, 39.5 ± 15.39 years) participated. The virtual PMRT scores from the two clinicians show high inter-rater reliability (78–90%) and high intra-rater reliability (71–90%) for all test conditions. More research is required to explore user preferences and effectiveness of the two control methods (rollers and mathematical model) and the display screens. Conclusions: The virtual driving simulator seems to be a promising tool for wheelchair driving assessment that clinicians can use to supplement their real-world evaluations.